Country adaptation of the 2010 World Health Organization recommendations for the prevention of mother-to-child transmission of HIV - Elena Ghanotakis; Lior Miller; Allison Spensley
The World Health Organization (WHO) revised its global recommendations on treating pregnant women infected with the human immunodeficiency virus (HIV) with antiretrovirals and preventing mother-to-child transmission (PMTCT) of HIV. Initial draft recommendations issued in November 2009 were followed by a full revised guideline in July 2010. The 2010 recommendations on PMTCT have important implications in terms of planning, human capacity and resources. Ministries of health therefore had to adapt their national guidelines to reflect the 2010 PMTCT recommendations, and the Elizabeth Glaser Pediatric AIDS Foundation tracked the adaptation process in the 14 countries where it provides technical support. In doing so it sought to understand common issues, challenges, and the decisions reached and to properly target its technical assistance. In 2010, countries revised their national guidelines in accordance with WHO's most recent PMTCT recommendations faster than in 2006; all 14 countries included in this analysis formally conducted the revision within 15 months of the 2010 PMTCT recommendations' release. Governments used various processes and fora to make decisions throughout the adaptation process; they considered factors such as feasibility, health delivery infrastructure, compatibility with 2006 WHO guidelines, equity and cost. Challenges arose; in some cases the new recommendations were implemented before being formally adapted into national guidelines and no direct guidance was available in various technical areas. As future PMTCT guidelines are developed, WHO, implementing partners and other stakeholders can use the information in this paper to plan their support to ministries of health.